2003
DOI: 10.1093/jxb/erg107
|View full text |Cite
|
Sign up to set email alerts
|

The micromorphology and protein characterization of rubber particles in Ficus carica, Ficus benghalensis and Hevea brasiliensis

Abstract: Rubber biosynthesis takes place on the surface of rubber particles. These particles are surrounded by a monolayer membrane in which the rubber transferase is anchored. In order to gain better insight into whether rubber particles from different plant species share common structural characteristics, the micromorphology of rubber particles from Ficus carica, Ficus benghalensis, and Hevea brasiliensis was examined by electron microscopy. Rubber particles of all three species were spherical in shape, and the size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 23 publications
5
63
1
Order By: Relevance
“…For instance, rubber particles isolated from Ficus carica and Ficus benghalensis did not contain SRPP proteins that cross reacted with rubber tree SRPP antisera, despite their ability to produce significant amounts of rubber (Singh et al, 2003). Russian dandelion, on the other hand, contains five SRPP-like genes, but only three of the encoded proteins have been detected in high amounts in purified rubber particles, and one of the genes shows a distinct organ and temporal gene expression pattern that is inconsistent with a role in rubber synthesis (Schmidt et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, rubber particles isolated from Ficus carica and Ficus benghalensis did not contain SRPP proteins that cross reacted with rubber tree SRPP antisera, despite their ability to produce significant amounts of rubber (Singh et al, 2003). Russian dandelion, on the other hand, contains five SRPP-like genes, but only three of the encoded proteins have been detected in high amounts in purified rubber particles, and one of the genes shows a distinct organ and temporal gene expression pattern that is inconsistent with a role in rubber synthesis (Schmidt et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In H. brasiliensis, they have bimodal size distribution in fresh latex. Large rubber particles (LRPs) and small rubber particles (SRPs) show diVerences not only in molecular weight distribution and molecular structure but also in their surface proteins (Bahri and Hamzah 1996;Sakdapipanich et al 1999;Ohya et al 2000;Singh et al 2003;Tarachiwin et al 2005). Immunogold electron microscopy has shown that 14-and 24-kDa proteins are localized abundantly on LRPs and SRPs, respectively (Bahri and Hamzah 1996;Singh et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Large rubber particles (LRPs) and small rubber particles (SRPs) show diVerences not only in molecular weight distribution and molecular structure but also in their surface proteins (Bahri and Hamzah 1996;Sakdapipanich et al 1999;Ohya et al 2000;Singh et al 2003;Tarachiwin et al 2005). Immunogold electron microscopy has shown that 14-and 24-kDa proteins are localized abundantly on LRPs and SRPs, respectively (Bahri and Hamzah 1996;Singh et al 2003). Coding genes of 14 kDa rubber elongation factor (REF) and 24 kDa SRP protein (SRPP) have been cloned (Attanyaka et al 1991;Goyvaerts et al 1991;Oh et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A positive effect was observed when small rubber particle protein (SRPP) and rubber elongation factor (REF), both proteins belonging to the REF superfamily, were added to washed rubber particles in H. brasiliensis (Oh et al, 1999;Wititsuwannnakul et al, 2003). As shown by immunogold labeling SRPPs are the most abundant proteins on rubber particles in H. brasiliensis (Oh et al, 1999;Singh et al, 2003;Sando et al, 2009). Other factors have not been identified as crucial for rubber biosynthesis so far.…”
Section: Rubber Biosynthesismentioning
confidence: 99%
“…These data suggest that the rubber transferase might indeed be a CPT. However, immunogold labeling of rubber particles from H. brasiliensis using an antibody raised against a synthetic peptide with a consensus sequence for a highly conserved region of CPTs failed to detect CPTs on rubber particles and unlike CPTs, the rubber transferase does not synthesize products of predetermined size but can synthesize products of a wide range of molecular mass (Castillion and Cornish, 1999;Singh et al, 2003;da Costa et al, 2005). However, the varying size of the natural rubber product was shown not to be solely dependant on the rubber transferase.…”
Section: Rubber Biosynthesismentioning
confidence: 99%